The association of effort-reward imbalance and asthma: findings from two cross-sectional studies - Loerbroks, Adrian; Herr, Raphael; Li, Jian; Bosch, Jos A.; Elstermann von Elster, Max Leonhard; Schneider, Michael; Angerer, Peter; Schmidt, Burkhard (International archives of occupational and environmental health, 2015)
Purpose There is evidence to suggest that work stress is positively associated with the occurrence of asthma. A limitation is that the small number of prior studies utilized unestablished work stress measures, thus constraining interpretation and generalizability. The present study re-examined this association by assessing work stress based on the well-established effort-reward imbalance (ERI) model.MethodsWe drew on data from two cross-sectional studies. Study 1 was conducted in a large pharmaceutical company in 2013 (n = 1,464). Study 2 was based on data from the 2011 wave of the population-based German Socio-Economic Panel (n = 8,388). ERI was assessed by validated questionnaires. Asthma was determined by self-report of a physician-based diagnosis. Associations between ERI or its subcomponents “effort”, “reward” and “overcommitment” (z scores or categorized) with asthma were estimated by logistic regression models and reported as adjusted odds ratios (ORs) with 95 % confidence intervals (CIs).ResultsA one standard deviation increase of the ERI score (reflecting higher work stress) was associated with a 22-48 % elevated odds of asthma (Study 1: OR 1.48, 95 % CI 1.13-1.95, and Study 2: OR 1.22, 95 % CI 1.10-1.36). Z score-based analyses of the separate ERI components generally suggested moderate associations of effort, reward and overcommitment with asthma in both studies (Study 1: OR effort 1.25, 95 % CI 0.95-1.64, OR reward 0.67, 95 % CI 0.51-0.87, OR overcommitment 1.32, 95 % CI 1.01-1.72; and Study 2: OR effort 1.21, 95 % CI 1.09-1.34, OR reward 0.83, 95 % CI 0.76-0.92, OR overcommitment 1.12, 95 % CI 1.01-1.25). Analyses of categorized exposures largely confirmed these observations.ConclusionsThis is the first study to demonstrate a link between an established work stress measure and asthma. Longitudinal studies are needed to determine the direction of these associations.